Інтродукція Cyperus esculentus L. в Лісостепу України - Smilyanets, N.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
Influence factors of Forest-Steppe on development of Cyperus esculentus L. and chemical structure tubers and oil-acid structure oil were studied. Introduction this species in Forest-Steppe is perspective.